Swearing Used in Richard Wrightâs Black Boy - Giyatmi, Giyatmi; WIjayava, Ratih; Widarwati, Nunun Tri (Register Journal, 2017)
This research aims at finding the types of swearing expressions and linguistic forms of English swearing used in Richard Wrightâs Black Boy. This is a descriptive qualitative research since it describes the phenomena of swearing used in the novel. The data of the research are all the conversations or sentences used swearing in the novel written by Richard Wright namely Black Boy as the main data source. The method of collecting data in this research is observation and teknik lanjut catat. After all the data had been collected then they are coded using the coding system such as data number/title of novel/chapter/page/data. There is no data reduction since all the data are analyzed in this research. This research used theory triangulation. Kind of swearing expressions found in this novel dealing with God and religion terms, name ofÂ  animals and plants, part of body, racial terms, stupidity terms, name of occupation, sexual terms, family terms. The linguistic forms of English swearing used in this novel are word, phrase, and clause. The swearing in the form of words consists of (1) noun referring to place, person, occupation, animal, and idea (2) verb and (3) adjective. Phrase consists of (1) noun phrase with swearing functioning as headword, modifier, and both headword and modifier, (2) adjective phrase with swearing functioning as modifier. Swearing expression is also found in the form of sentence.Â Â Â